2015
DOI: 10.1016/j.gie.2014.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent intestinal metaplasia after radiofrequency ablation for Barrett’s esophagus: endoscopic findings and anatomic location

Abstract: Background Radiofrequency ablation (RFA) is a safe and effective treatment for Barrett’s esophagus (BE) that results in high rates of complete eradication of intestinal metaplasia (CEIM). However, recurrence is common after CEIM and surveillance endoscopy is recommended. Neither the anatomic location nor the endoscopic appearance of these recurrences is well described. Objective The objectives of this study are to describe the location of histologic specimens positive for recurrence after CEIM and the testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 23 publications
(22 reference statements)
2
35
0
2
Order By: Relevance
“…Eighty per cent of recurrences in the tubular oesophagus were visible endoscopically,10 and random biopsies >1 cm proximal to the GOJ had no yield for any recurrence 15. Data from the current larger multicentre cohort show that 82% of tubular oesophageal recurrences were visible, and the yield of random biopsies >1 cm proximal to the GOJ was extremely low (1.2% yield for any recurrence and 0.2% for dysplastic recurrence).…”
Section: Discussionmentioning
confidence: 69%
“…Eighty per cent of recurrences in the tubular oesophagus were visible endoscopically,10 and random biopsies >1 cm proximal to the GOJ had no yield for any recurrence 15. Data from the current larger multicentre cohort show that 82% of tubular oesophageal recurrences were visible, and the yield of random biopsies >1 cm proximal to the GOJ was extremely low (1.2% yield for any recurrence and 0.2% for dysplastic recurrence).…”
Section: Discussionmentioning
confidence: 69%
“…This included 21 RFA studies that reported 603 cases of IM recurrence in 3186 patients over 5741 patient-years of follow-up. 9,12,14,15,18,21,22,27,29,30,32,39-41,43,47,49,51,53,54 Figure 1 shows the schematic diagram of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 41 included studies, the primary endoscopic treatment modality was RFA in 21 studies, 9,12,14,15,18,21,22,27,29,30,32,39-41,43,47,49,51,53,54 APC in 7 studies, 33,34,36,45,46,48,52 EMR in 7 studies, 20,21,31,37,42,44,50 PDT in 2 studies, 7,19 multipolar electrocoagulation in 2 studies, 13,28 laser in 1 study, 35 and cryotherapy in 1 study. 38 Twenty-three studies were from North America, 9,12,14,15,18-20,22,27,30,32,35,37-39,41-44,47,53,54 15 studies were from Europe, 7,13,21,31,33,34,40,45,46,48-52 and 1 study each was from South America, 28 Africa, 36 and the Asia-Pacific. 29 Four studies included NDBE patients only, 13,28,34,52 and 16 studies included only DBE ± early neoplasia patients, 7,19-21,29,31,37,39,40,42,44,49,51,53,54 with the remainder including NDBE and DBE patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations